2020
DOI: 10.1038/s41598-020-75625-1
|View full text |Cite
|
Sign up to set email alerts
|

SASH1 is a prognostic indicator and potential therapeutic target in non-small cell lung cancer

Abstract: SASH1 (SAM and SH3 domain-containing protein 1) is a tumor suppressor protein that has roles in key cellular processes including apoptosis and cellular proliferation. As these cellular processes are frequently disrupted in human tumours and little is known about the role of SASH1 in the pathogenesis of the disease, we analysed the prognostic value of SASH1 in non-small cell lung cancers using publicly available datasets. Here, we show that low SASH1 mRNA expression is associated with poor survival in adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…87,120,122 Interestingly, Burgess et al recently demonstrated that increasing SASH1-protein levels by addition of chloropyramine is inhibiting the proliferation of lung cancer cells in a SASH1-dependent manner. 125 Moreover, this observation was accompanied by increased sensitivity of cancer cells toward cisplatin treatment. Therefore, the drug-mediated elevation of SASH1 concentrations should be considered as a potential future tool in anticancer therapy.…”
Section: Sash1 In Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…87,120,122 Interestingly, Burgess et al recently demonstrated that increasing SASH1-protein levels by addition of chloropyramine is inhibiting the proliferation of lung cancer cells in a SASH1-dependent manner. 125 Moreover, this observation was accompanied by increased sensitivity of cancer cells toward cisplatin treatment. Therefore, the drug-mediated elevation of SASH1 concentrations should be considered as a potential future tool in anticancer therapy.…”
Section: Sash1 In Cancermentioning
confidence: 99%
“…Interestingly, Burgess et al recently demonstrated that increasing SASH1‐protein levels by addition of chloropyramine is inhibiting the proliferation of lung cancer cells in a SASH1‐dependent manner 125 . Moreover, this observation was accompanied by increased sensitivity of cancer cells toward cisplatin treatment.…”
Section: Sash1/sly3mentioning
confidence: 99%
See 2 more Smart Citations
“…In OS, circ-ITCH sponges miR-524 to up-regulate RASSF6, inducing OS cell death and limiting its proliferation, according to Zhou et al (Zhou W. et al, 2021). SAM and SH3 domain containing protein 1 (SASH1) is a tumor-suppressive protein that can regulate cell apoptosis and proliferation (Burgess et al, 2020). Circ-ITCH can suppress glioma growth and invasion by up-regulating SASH1 by targeting miR-106a-5p (Chen et al, 2021).…”
Section: Regulating Cell Cycle-related Proteinsmentioning
confidence: 99%